PENGEMBANGAN MEDIA PEMBELAJARAN PAI MELALUI ANIMASI DENGAN APLIKASI KINEMASTER BERBASIS ANDROID - mabrur, muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
ABSTRACTTechnology can be utilized in the learning process both in developing learning tools and learning media. Based on this, the author formulates the problem,